1979
DOI: 10.1172/jci109381
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Immunoreactivities and Amino Acid Profile in Plasma of Duodenopancreatectomized Patients

Abstract: A B S T R A C T Glucogon immunoreactivity (IRG) was measured in plasma of duodenopancreatectomized subjects with a nonspecific (K-4023) and a specific (30-K) glucagon antiserum. After an overnight fast, plasma IRG (K-4023) was significantly (P < 0.05) higher in the subjects without pancreas, averaging 782±79 (SEM) pgeq/ml, than in the controls (482±80 pgeq/ml). IRG (30-K) of 162±68 pglml did not change during an infusion ofarginine (450 mg/kg per 40 min). Insulin deprivation during 3 d in one patient did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
(48 reference statements)
3
28
0
Order By: Relevance
“…That is not a new finding (4 -6). Assuming comparable suppression of ␤-cell insulin and ␣-cell glucagon secretion by octreotide, it suggests that the antibody used to measure glucagon recognizes species in addition to biologically active 3,500-Da glucagon, a phenomenon well documented with earlier antibodies (e.g., [25][26][27][28][29]. Clearly, however, given lower rates of glucose production and plasma glucose concentrations during octreotide infusion with insulin replacement, octreotide produced biological glucagon deficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…That is not a new finding (4 -6). Assuming comparable suppression of ␤-cell insulin and ␣-cell glucagon secretion by octreotide, it suggests that the antibody used to measure glucagon recognizes species in addition to biologically active 3,500-Da glucagon, a phenomenon well documented with earlier antibodies (e.g., [25][26][27][28][29]. Clearly, however, given lower rates of glucose production and plasma glucose concentrations during octreotide infusion with insulin replacement, octreotide produced biological glucagon deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in the short-term, factors in addition to these hormones must be involved in maintenance of the postabsorptive glucose level. Nonetheless, chronic insulin and glucagon deficiencies (e.g., in pancreatectomized humans who have low insulin levels and little or no circulating biologically active 3,500-Da glucagon [25][26][27][28][29]) cause diabetes. That indicates that among the pancreatic islet hormones, insulin plays a predominant role in maintenance of the postabsorptive plasma glucose concentration and further that elevated glucagon levels are not a requisite condition for the development of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with pancreatic diabetes, System A amino acids and gluconeogenic amino acids showed higher values than those in patients with primary diabetes, and their amino acid profile resembled that in diabetic patients with total pancreatectomy (Boden et al 1974;Muller et al 1979). Furthermore, we studied the correlation between plasma glucagon and plasma amino acids as the factors possibly contributing to changes in amino acid level.…”
Section: Discussionmentioning
confidence: 98%
“…It has been established that the plasma glucagon level becomes abnormally low in patients with total pancreatectomy (Muller et al 1974). In this case, plasma levels of gluconeogenic amino acids such as Ala and Ser and ureagenetic amino acids such as Orn and Arg increase (Muller et al 1979). It has been reported that plasma amino acid levels in such cases would tend to normalize after the administration of glucagon (Boden et al 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation